You're either with us or against us! Moral conviction determines how the politicized distinguish friend from foe. (July 2017) - Zaal, Maarten P.; Saab, Rim; O'Brien, Kerry; Jeffries, Carla; Barreto, Manuela; van Laar, Colette
Three studies investigated how politicized collective identification affects individuals' reactions towards others. We hypothesized that a strong politicized identity tends to be accompanied by a moral conviction about the politicized cause, which in turn determines how the politicized respond to those less committed to their cause. Consistent with this, Study 1 showed that politicized (feminist) identification is associated with lower identification with women who place moderate (vs. high) moral value on gender equality. Study 2 showed that politicized identification was associated with negative emotions towards people who disagree with this cause and this was mediated by the extent to which participants saw supporting the activist goal as morally obligatory. Study 3 showed that politicized identification, to the extent to which it implied holding a moral conviction about the activist cause, is associated with a desire for more social distance to an attitudinally dissimilar other, but not from an attitudinally similar other.